Peran Orang Tua Teradap Prestasi Belajar Siswa Sd Al-Furqan Jember - Sofyan Rofi (STAIFAS-Press, 2016)
Objective of the study : (1) to know how far parentsâ€™ role student learning achievement at Al-furqan Jember, (2) how to correlation between parent of student and school at SD Al-Furqan Jember. This study was done at SD Al-Furqan Jember, by using qualitative approach. Data collecting technique was done by : (1) deep interview, (2) documentation. While checking up data validity was done by cross check with triangulation technique and colleagues discussion. Data analysis was done by (1) data reduction, (2) data presentation, (3) withdrawal of conclusion. From data analysis was found that parent has so central to student learning achievement, because education in school is still not enough increase student learning achievement. With the parentsâ€™ role so not just teacher wo strive to increase student learning achievement however parent does advising to their child by join the course. While relation between student old fellow with school intertwin intensive communications with meeting of pupil sponsor mothers in majelis taâ€™lim that conducted by institution of Al-Furqan Jember. From all data and the result of research finding is found that parentsâ€™ role is so necessary to student learning achievement of SD Al-Furqan Jember and relation among student old fellow with school is very good and communicative. As for researcher suggestion is school have to be more improve role of old fellow to student learning process, in order to student achievement progressively mount.Â Â Â Â Â Key word : Parent, learning achievement